Modelling effects of degree of crystallinity on mechanical behavior of semicrystalline polymers - Dusunceli, Necmi; Colak, Ozgen U. (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Viscoplasticity theory based on overstress (VBO) which is one of the unified state variable theories is extended to account for crystallinity ratio (empty set) on mechanical behavior of sernicrystalline polymers. The modifications on VBO are done considering the semicrystalline polymeric materials somewhat as a composite material since it consists of amorphous and crystalline phases. Amorphous and crystalline phase resistances are arranged in two different analog models: amorphous stiffness and flow are in parallel and series with crystalline phase. Apart from many existing work in the literature, not only uniaxial loading are modeled but also creep and relaxation behaviors are simulated for a hypothetical material. It is shown that when amorphous and crystalline phase resistances acting in parallel are considered in the model, creep, relaxation and uniaxial loading and unloading behaviors can be simulated well using the modified VBO. In addition, uniaxial compression loading and unloading behavior of highly crosslinked ultra-high molecular weight polyethylene (UHMWPE) and creep behavior of polytetrafluoroethylene (PTFE) with different crystallinity ratios are simulated using the proposed VBO model where amorphous and crystalline phases are parallel. Simulation results are compared to the experimental data by Kurtz et al. (2002) and Sun et al. (2005) [Kurtz, S.M., Villarragaa, M.L., Herra, M.P., Bergstrom, J.S., Rimnacc, C.M., Edidin, A.A., 2002. Thermomechanical behavior of virgin and highly crosslinked ultra-high molecular weight polyethylene used in total joint replacements. Biomaterials 23, 3681-3697; Sun, H., Cooke, R. S., Bates, W. D., Wynne, K.J., 2005. Supercritical CO, processing and annealing of polytetrafluoroethylene (PTFE) and modified PTFE for [GRAPHICS] enhancement of crystallinity and creep resistance. Polymer 46, 8872-8882] respectively and good match with experimental data is obtained. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: crystallinity ratio; viscoplasticity; creep; relaxation; loading-tin loading; MOLECULAR-WEIGHT POLYETHYLENE; HIGH-DENSITY POLYETHYLENE; DEFORMATION-BEHAVIOR; CONSTITUTIVE MODEL; POLY(ETHYLENE-TEREPHTHALATE); Engineering; Materials Science; Mechanics